Structural implications of ionic conduction in LaAlO3–Ce0.8Gd0.2O2-δ composite solid electrolyte - Verma O.N.; Yadav A.; Pandey R.; Jire L Hmar J.; Kumar V.; Singh P. (My University, 2025)
Investigations were done on the combinations of perovskites and fluorite structured composite electrolyte materials to check the possible enhancement of the ionic conductivity. For this purpose, the compounds, LaAlO3 (LAO) and Ce0.8Gd0.2O2- (CGO) were mixed in the weight ratios of 3:1, 2:2, and 1:3 to develop cost-effective composite electrolyte materials. Conductivity spectroscopy techniques were used to examine the dc electrical transport properties. Thermal properties were investigated using thermogravimetry analysis. Fourier transform spectroscopy was employed for bond structural study, while an X-ray diffractometer pattern analysis was employed to ensure the formation of composite structure. Scanning electron microscopy and energy dispersive X-ray spectroscopy studies confirm dense microstructure by a suitable weight proportion of component, homogeneous grain dispersion, and elemental confinement. The electrical behavior of composite electrolytes was demonstrated by electrochemical impedance spectroscopic analysis methods, which instigate the highest value of the conductivity of the order of 0.14x10−2 S cm−1 and lower activation energy value (0.72 eV) at temperature 700 °C for composite with LAO-CGO weight ratio of 1:3. © 2024 Elsevier Ltd and Techna Group S.r.l.